2004
DOI: 10.1002/cbf.1166
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of carbon tetrachloride‐induced nephropathy by melatonin administration

Abstract: The aim of this study was to investigate possible protective effects of melatonin on carbon tetrachloride (CCl4)-induced renal damage in rats. A total of 24 animals were divided into three equal groups: the control rats received pure olive oil subcutaneously, rats in the second group were injected with CCl4 (0.5 ml kg-1, s.c. in olive oil) and rats in the third group were injected with CCl4 (0.5 ml kg-1) plus melatonin (25 mg kg-1, s.c. in 10% ethanol) every other day for 1 month. At the end of the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
3
21
0
2
Order By: Relevance
“…In addition, in animals treated with LPS, melatonin abolished the increment in lipid peroxidation and managed to offset the hepatic degenerative changes. In experiments in vivo, the administration of melatonin prevented carbon tetrachloride (CCl 4 ) induced lipid peroxidation in the kidney and liver 35 . There are many characteristics which melatonin possesses which aids its ability to inhibit lipid peroxidation: (a) it is 38 which propagate peroxidation, as well as the highly reactive singlet oxygen 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in animals treated with LPS, melatonin abolished the increment in lipid peroxidation and managed to offset the hepatic degenerative changes. In experiments in vivo, the administration of melatonin prevented carbon tetrachloride (CCl 4 ) induced lipid peroxidation in the kidney and liver 35 . There are many characteristics which melatonin possesses which aids its ability to inhibit lipid peroxidation: (a) it is 38 which propagate peroxidation, as well as the highly reactive singlet oxygen 39 .…”
Section: Discussionmentioning
confidence: 99%
“…a hydroxyl radical and a peroxyl radical scavenger. 29,30 It has also been shown that when animals and tissues are subjected to lipid peroxidation, melatonin causes a substantial protection against the oxidative destruction of lipids. 31 However, to our knowledge, there is no experimental study concerning the protective effects of melatonin against neuronal damage in prefrontal cortex induced by HCHO.…”
Section: Introductionmentioning
confidence: 99%
“…In certain studies (6,16), an antioxidant effect was obtained when 10 mg/kg MLT was administered; as this dosage was the dose we used, however in some studies (18), it was reported that, antioxidant effect was obtained only when a dose of 25 mg/kg was administered. In the present study, both in the liver and kidney tissues, Vitamin C group MDA values were found quite close to the MDA values of the control group when compared with other groups.…”
Section: Discussionmentioning
confidence: 98%
“…However the pathology related with renal function failure that is stimulated by CCl 4 remains controversial. As kidneys have an affinity against CCl 4 , and as they contain predominantly, cystochrome p450 in the cortex, it is very possible that CCl 4 contributes a lot to nephrotoxicity (18). Even though Rincon et al (19) demonstrated that the effects of CCl4 on the structure and function of kidneys are dependant to the functional state of the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation